Perceptions of Good Jobs : Analytical Report--Urban Cairo and Rural Fayoum, Egypt - Kebede, Tewodros (World Bank, Washington, DC, 2013)
This study shows how jobs are perceived in Egypt by exploring beyond earnings, health benefits, and pension plans that characterize a “good job” to focus on the features that increase living standards, productivity growth, and social cohesion. In both urban Cairo and rural Fayoum, men are more likely to work than women, middle aged people more frequently than younger and older, while prolonged health problems hinder people from participating in the labor market. Urban dwellers are less likely to work, though wage jobs contribute to household wealth creation. Jobs offering stability, benefits, and prestige are preferredin both rural and urban areas, but there is a clear divide in perception of job types, with farming considered as the easiest to pursue in rural areas. Assessments of job satisfaction show urban dwellers as less satisfied than rural dwellers. Job holders exert decision-making authority in households, increasing the overall perception of job satisfaction and social status. Jobs consist mainly of manual labor—dominated by routine work with a relatively high level of autonomy—and a “good,” more meaningful job requires a shift from manual toward more cognitive work as well as from routine toward more creative tasks. Rural households exhibit higher levels of both social confidence and confidence in institutions than urban dwellers, showing the importance of wage employment in increasing social cohesion.